KEEFEKTIFAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA - Mariya Mariya (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research was conducted at 015 Public Elementary School Geringging Jaya, Kuantan Singingi Regency. The subjects of this study were 18th grade V students consisting of 8 male students and 10 female students. The purpose of this study is to improve student science learning outcomes by applying a problem based learning model. This research consists of planning, implementing, observing, and reflecting. The results showed, seen from the average value of a student's base score of 63.2 with 10 students completing as many as a percentage of 55.5% experienced an increase in the first cycle with an average value of students becoming 74.3 with students completing being 14 people with a percentage of 77.7%. Whereas in the second cycle again menngkata with an average value of 86.7 with students who finished up to 16 people with a percentage of 88.8%.Can the researchers conclude that the application of the problem based learning model is effective in improving the learning outcomes of science students in grade at 015 Public Elementary School Geringging Jaya